ANALISIS PELAKSANAAN PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA BAGI ORANG DENGAN GANGGUAN JIWA BERAT DI PUSKESMAS (STUDI KASUS SKIZOFRENIA DI PUSKESMAS KEDUNGMUNDU KOTA SEMARANG) - Lathifah Safaatul Uzhma; Ayun Sriatmi; Sutopo Patria Jati; Antono Suryoputro (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Mental health is one of the important components to get health as a whole. Mental health is included in one indicator of Minimum Service Standards (SPM) and in the Healthy Family Indicator (IKS) PIS-PK which both focus on severe ODGJ. The Annual Life Report of the Semarang City Health Office shows an increase in the number of cases of severe mental disorders (Schizophrenia) in the Semarang City Health Center each year. In 2017 the city of Semarang has reached the target of 100% SPM in health services for severe ODGJ. But based on data from the Social Service of Central Java Province in Semarang in Semarang, there were 325 persons with mental disabilities (psychotic) and 67 children with mental disabilities (psychotic) who were reported by the community and had not received health services. This study aims to describe the implementation of PIS-PK for people with severe mental disorders in the Semarang City Health Center, especially in cases of schizophrenia in Kedungmundu Health Center with a system theory approach. This qualitative study uses in-depth interview methods. The results showed that the PIS-PK helped in the ODGJ data collection especially in cases of schizophrenia. The ODGJ program was helped by the PIS-PK, because there was no specific program intended for ODGJ. But further interventions for ODGJ have not been implemented in PIS-PK activities. Further interventions will only be carried out on the 3 most problems that arise in the community and ODGJ Severe (Schizophrenia) problems are not included in that. Further interventions can be carried out by crossing collaboration programs between PIS-PK and ODGJ programs, so that IKS and SPM can be achieved simultaneously. In addition, there is no synchronization between SPM report data and ODGJ data on PIS-PK. So that the data is not yet able to show the case in real terms. Even though ODGJ data in PIS-PK, can be a reference in taking intervention in the community. Furthermore, the ODGJ case finding can be helped by maximizing the SRQ 29 form early detection.